Evaluation of clinical results in patients undergoing laparoscopic nephroureterectomy - Hamada, Shinsuke (Hinyokika kiyo. Acta urologica Japonica, 2013)
We evaluated the efficacy of laparoscopic radical nephroureterectomy (LNUx) by comparing the clinical results in 55 patients undergoing LNUx at the National Defense Medical College since 2001 with those in patients undergoing open radical nephroureterectomy (ONUx) there over the same period. LNUx was performed successfully in 54 of the patients, but one patient required conversion to ONUx. The mean operating time for LNUx was not significantly different from that for ONUx, and the mean estimated blood loss during LNUx was significantly lower than that during ONUx. Major complications occurring early in our laparoscopic series of cases were injury of the duodenum and bleeding from the inferior vena cava. Oncological outcomes were compared between LNUx (n＝50) and ONUx (n＝50) in patients with pathologically-confirmed urothelial carcinoma. The pT stage, histological grade, percentage of lymph node dissection and percentage of high grade hydronephrosis did not differ significantly between the two groups. Because the intravesical recurrence-free survival rates, extravesical recurrence-free survival rates, and disease specific survival rates were also similar in the two groups, we concluded that LNUx is an appropriate treatment for upper urinary tract urothelial carcinoma